VALIDITY OF LEARNING MEDIA IN REACTION RATE MATERIAL - Ahlan Riwahyu Habibi; Rudiana Agustini (Universitas Negeri Surabaya, 2022)
Abstact.This research is aimed at knowing the validity of learning media in reaction rate matter. The type of research method that is used is ADDIE (Analysis, Design, Development, Implementation and Evaluation) but in this research is limited to Development step. The validation test was conducted by a chemistry lecturer from Unesa by filled the questionnare. The validity of learning media can be scored from construct validity and content validity. Based on the validation result, the construct validity score average is 4.39 which is categorized into very good. The content validity score average is 4.14 which is categorized into good. Based on the validation result, it can be concluded that the learning media was declared to be used as the reaction rate of learning media.Keywords: Learning Media, The Validity, Reaction Rate